Association between TH2 Cytokine Gene Polymorphisms and Risk of Bullous Pemphigoid. (17th February 2022) - Tabatabaei-Panah, Pardis-Sadat; Moravvej, Hamideh; Alirajab, Marzieh; Etaaty, Ahmad; Geranmayeh, Maryam; Hosseine, Farzaneh; Khansari, Atousa; Mahdian, Mohadeseh; Mirhashemi, Mahsa; Parvizi, Samira; Sakhaie, Fatemeh; Ludwig, Ralf J.; et al.
ABSTRACT: Background: T-helper 2 (Th2)-associated cytokines are involved in the pathogenesis of bullous pemphigoid (BP), an autoimmune skin disease. Increased expression of Th2 cytokines such as interleukin-4 (IL-4), IL-5, IL-6, IL-10, and IL-13 have been observed in serum, skin biopsies and/or blister fluid. This study aimed to uncover a possible association between Th2 cytokine genetic variations and susceptibility to BP. Methods: In a cohort study, blood samples of BP patients and controls were obtained and variations in IL-4 (rs2243250 and rs2070874), IL-4R (rs1805010), IL-5 (rs2069812), IL-6 (rs1800795), IL-10 (rs1800896, rs1800871, and rs1800872), and IL-13 (rs1800925 and rs20541) were genotyped by PCR-RFLP assays. Furthermore, quantitative expression levels of IL-13 gene were evaluated by real-time RT-PCR analysis. Results: Among the studied variations, a significantly higher frequency of the C-allele was observed in IL-13 gene variation (rs1800925) in the healthy individuals than BP patients. This may indicate a protective effect of C-allele on predisposition to BP. Considering individuals carrying polymorphic genotypes compared to wild genotype, the minor G-allele of IL-4R rs1805010 and A-allele of IL-13 rs20541 had a promotive and protective effect, respectively, on predisposing to the development of BP. No significant difference in IL-13 mRNA expression was detected between BP patients and healthy individuals. Conclusions: Our results indicate that IL-13 rs1800925 variation may be a protective genetic marker for the development of BP. Given this preventive effect against BP, therapeutic strategies could potentially be developed interfering with the functions of IL-13 cytokine, which seems to be integral in the pathogenesis of eosinophilic inflammatory disorders, such as BP.